Ethnic Variation in Lipid Profile and Its Associations with Body Composition and Diet: Differences Between Iranians, Indians and Caucasians Living in Australia - Meshkini, M.; Alaei-Shahmiri, F.; Mamotte, Cyril; Earnest, Jaya (2016)
Dyslipidaemia is a known risk factor for developing cardiovascular disease. The impact of ethnicity on variations in lipid patterns has been studied in certain racial and ethnic groups with limited data on other ethnicities, particularly Asian subgroups. This cross-sectional study evaluated the ethnic variation in lipid profile and its association with body composition and diet in ninety-one overweight and obese Australians of European (n = 32), Indian (n = 28) and Iranian (n = 31) ancestries. Different measures of total and truncal adiposity were assessed using the method of whole body dual energy X-ray absorptiometry. The results showed that serum total cholesterol (TC) and low density lipoprotein cholesterol (LDL-chol) levels in Iranians were significantly lower than in Europeans and Indians. Both Iranian and Indian groups exhibited lower mean high density lipoprotein cholesterol (HDL-chol) relative to Europeans. Triglycerides (TG) and HDL-chol, but not TC and LDL-chol, were significantly associated with different truncal adiposity measurements; however the degree of associations varied in ethnic groups. Regression analysis showed ethnicity as a significant predictor of TC (p = 0.01), TG (p = 0.03) and HDL-chol (p = 0.04), after controlling for potential confounders. However, LDL-chol was significantly associated with the intake of total (p = 0.005), and saturated fats (p = 0.004), which were also other significant determinants of serum TC (p = 0.04 and p = 0.02, respectively). In conclusion, ethnicity was a strong predictor of serum lipids, except LDL-chol which was significantly determined by dietary fat intake. Prevention and management of obesity, particularly abdominal adiposity may effectively reduce the risk of low HDL-chol reported in Iranians and Indians.